Mitigating Strategies for Nurses' Emotional Exhaust based on Technology-Based Assessment: A Systematic Review - Laily, Anis khilya khasnatil; Dian Handayani; Heni Dwi Windarwati (Journal Of Nursing Practice, 2026)
Background: Most nurses report experiencing emotional exhaustion due to high job demands, a condition that not only affects individuals but also impacts the overall healthcare system. The utilization of health information systems offers significant potential in detecting, measuring, and managing emotional exhaustion among healthcare professionals through comprehensive data analysis, thus improving individual well-being and the quality of healthcare services. Purpose: The objective of this systematic review is to explore indicators of emotional exhaustion and strategies to address it. Methods: This review was developed based on the Joanna Briggs Institute (JBI) methodology and presented according to PRISMA. Three databases, PubMed, ScienceDirect, and ProQuest, were used as sources to search for studies in English. The research obtained with the criteria of discussing health information systems and emotional exhaustion, original research, full text, and published between 2019-2024. Out of 1,782 identified articles, 15 articles were selected for in-depth analysis. Results: Through this systematic review, it was found that HIS can be used to measure emotional exhaustion through behavioural, performance, and organizational dimensions. These indicators can be identified through the analysis of data stored in HIS. In addition, HIS can also support mitigation efforts through increased work efficiency, employee health management, and organizational support. Conclusion: Detecting the condition of emotional exhaustion and understanding how to mitigate it are competencies required to support the smooth and quality delivery of nursing care.